2018
DOI: 10.18433/jpps30100
|View full text |Cite
|
Sign up to set email alerts
|

A Case for Alpha-Lipoic Acid as an Alternative Treatment for Diabetic Polyneuropathy

Abstract: -Purpose: The aim of this systematic review is to evaluate current evidence of alpha-lipoic acid (ALA) regarding efficacy, safety, and cost to accurately compare it with other diabetic polyneuropathy (DPN) treatments. The intention is to provide recommendations on future research and to promote utilization of ALA in the United States (US). Methods: A literature search was conducted on three databases: Scopus, PubMed, and Web of Science. The following criteria were used to select studies: (1) randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Our study proved that the greatest improvement regarding DNS score, NDS and the pain intensity on the visual analogue scale was achieved in the group of patients that were given Benfotiamine and ALA treatment. The most important observation in the medical literature is that ALA acts not only on the mechanisms that maintain and lead to the progression of DSPDN, but also improves the symptoms, meaning that it plays a double role of pathogenic and symptomatic treatment [40].…”
Section: Estimation Of Treatment Efficacy By the Patients Glycaemic mentioning
confidence: 99%
“…Our study proved that the greatest improvement regarding DNS score, NDS and the pain intensity on the visual analogue scale was achieved in the group of patients that were given Benfotiamine and ALA treatment. The most important observation in the medical literature is that ALA acts not only on the mechanisms that maintain and lead to the progression of DSPDN, but also improves the symptoms, meaning that it plays a double role of pathogenic and symptomatic treatment [40].…”
Section: Estimation Of Treatment Efficacy By the Patients Glycaemic mentioning
confidence: 99%
“…Collectively, these trials show that intravenous a-lipoic acid (600 mg/ day) improved neuropathic symptoms and signs after 3 weeks. Furthermore, oral treatment for 5 weeks (600 mg/day) ameliorated pain, paresthesia and numbness at a clinically important level 22,31,32,[41][42][43][44][45][46][47][48] . In the Neurological Assessment of Thioctic Acid in Diabetic Neuropathy ( NATHAN ) 1 trial, including 460 participants with diabetes and mild-to-moderate largely asymptomatic DSPN, neuropathic deficits were improved with a-lipoic acid after 4 years 32,41,47 .…”
Section: Pathogenesis-derived Pharmacotherapymentioning
confidence: 99%
“…In view of the recognized roles of MNs in mitochondrial functions, a body of literature has focused on the beneficial outcomes of treating diabetic patients with each MN, leading to clinical improvements following patients' treatment with ALA, or coQ10, or CARN, as summarized in Table 1 (reviewed in [7]). Since early clinical studies in the 1990s, ALA has been demonstrated to provide adjuvant support in ameliorating the clinical conditions of T2D patients [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], with the recognition of ALA as a prescription drug in diabetic patients by the German Drug Index [49]. Other clinical studies have investigated the adjuvant effects of either coQ10 [50][51][52][53][54][55] or CARN (or acyl-CARN) [56][57][58][59][60][61][62][63][64][65] in T2D patients, by improving blood pressure and glycemic control.…”
Section: Type 2 Diabetesmentioning
confidence: 99%